Kemampuan Berpikir Analogis Siswa SMP dalam Menyelesaikan Masalah Aljabar Ditinjau dari Tipe Kepribadian - Anwari, Nabilah Chairunisa; Wijayanti, Pradnyo (Universitas Negeri Surabaya, 2024)
This study aims to describe analogical thinking abilities of junior high school students in solving algebra problems with guardian, artisan, rational and idealist personalities. The type of research used is qualitative descriptive research. The subjects in this study are 1 student for each personality type, namely guardian, artisan, rational, and idealist. Data is collected using test and interview techniques. The instruments used include personality type tests, analogical thinking ability tests, and interview guidelines. Data is processed using Miles and Huberman's techniques, which include three stages: data reduction, data presentation, and drawing conclusions. The research results indicate that students with guardian and artisan personality types can master all indicators of analogical thinking abilities. These students can identify source problems and target problems by searching for characteristics or problem structures, infer concepts present in the source problem, find connections between both problems, and implement ideas or solution methods from the source problem to solve the target problem. Students with a rational personality type can master the inferring indicator, meaning they can infer concepts present in the source problem. Meanwhile, students with an idealist personality type can master both the inferring and mapping indicators, meaning they can infer concepts present in the source problem and find connections between the source and target problems.